A New Model Based on 25-Hydroxyvitamin D3 for Predicting Active Crohn’s Disease in Chinese Patients - Lin, Sinan; Wang, Ying; Li, Li; Chen, Peng; Mao, Ren; Feng, Rui; Qiu, Yun; He, Yao; Chen, Baili; Zeng, Zhirong; Chen, Minhu; Zhang, Shenghong (Mediators of Inflammation, 2018)
Background. The association between vitamin D3 and activity of Crohn’s disease (CD) is unclear in Chinese patients. In this study, we aimed to evaluate the correlations between serum levels of 25-hydroxyvitamin D3 (25(OH)D3) and disease activity and predict active disease based on vitamin D status. Methods. Between January 2014 and December 2017, 346 CD patients from the First Affiliated Hospital of Sun Yat-sen University were recruited and categorized into a group with 25(OH)D3 ≤ 20 ng/ml and a group with 25(OH)D3 > 20 ng/ml. The clinical characteristics, medication, and health-care needs were compared between the groups. The correlations among 25(OH)D3 and routine serum biomarkers and disease activity were examined. The predictive efficiency of 25(OH)D3 and other biomarkers for active diseases was also explored using receiver-operating characteristic (ROC) curve analysis. A new predictive model, −5∗25OHD3+2∗Hb+ESR, and a nomogram were established using Logistic Regression. Results. Patients with 25(OH)D3 ≤ 20 ng/ml had higher serum levels of C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and platelets (PLT) and lower levels of hemoglobin (Hb) and albumin (ALB). Serum levels of 25(OH)D3 were inversely correlated with the score of Crohn’s Disease Activity Index (CDAI) (rs=−0.608). ROC analysis showed a better predictive value of −25(OH)D3 and the new model with areas under curve (AUC) of 0.804 and 0.879, respectively, than those of CRP (0.693) and ESR (0.713) in disease activity. A nomogram for prediction was established with a c-index of 0.882. Conclusions. Serum levels of 25(OH)D3 negatively correlated with CD activity in Chinese patients. The new model and a nomogram based on 25(OH)D3 showed a better efficiency in predicting disease activity in CD patients but warrants further study.